Teaching English to Very Young Learners in Kindergartens in Myanmar - Po, Ei Thet Hmoo; Pransiska, Rismareni (ALSYSTECH Journal of Education Technology, 2023)
The purpose of this study is to determine the Implementation of Teaching English To Very Young Learners in kindergartens in Myanmar. The subjects of this study are the early childhood education teachers from Myanmar. The research problem is going to investigate is the practice of teaching in Myanmar particularly on the methods of teaching tend to implement in Yangon city Myanmar. Data is obtained through questionnaires. The Research findings on teachers’ involvement are first briefly reviewed, and then the analyses using the data are discussed to identify the trend and practice of teaching English in Kindergarten. It can be concluded that the planning, methods, the analysis used in this paper are in accordance with the references.